Incidentally Detected High SSTR Expression in Uterine Leiomyoma on DOTANOC PET/CT. (January 2022) - Datta Gupta, Shreya; Kaushik, Prateek; Ramteke, Prashant; Mallik, Abhishek Kumar; Krishna, Asuri; Sharma, J.B.; Damle, Nishikant Avinash
Abstract : Abstract: A 38-year-old woman with a 2-month history of per vaginal bleeding and episodes of palpitations, headache, and vomiting underwent 68 Ga-DOTANOC PET/CT for evaluation, which revealed a left suprarenal mass and a large uterine mass, both of which were intensely tracer avid. Histopathology of the masses after surgery revealed a left pheochromocytoma and uterine leiomyoma. SSTR-expressing leiomyoma is an uncommon finding and must be kept in mind as a differential diagnosis of DOTANOC-avid uterine mass.